Feeding of game animals on «aguajales» in the Reserva Nacional Pacaya Samiria (Iquitos, Peru) - Aquino, Rolando (2005)
This report contains information related to the game mammals that inhabit the palm swamps (aguajales) of the flooded forests of the Reserva Nacional Pacaya Samiria and their interrelation with the food plants. It is based on censuses by transects in aguajales of recent origin and semi-eutrophic aguajales. 24 species of game mammals were registered making uses of the aguajales; of them, the primates were the most representative and the great abundance in both aguajales types. Among the primates, the Squirrel monkey (Saimiri boliviensis E. Geoffroy & R. de Blainville) and the brown capuchin monkey (Cebus apella Linnaeus) were the most abundant in aguajales of recent origin (350 individuals/km2 and 90 individuals/km2 , respectively), while the white-fronted capuchin monkey (Cebus albifrons Humboldt) it was the most abundant in aguajal semi-eutrofizado (90 individuals/km2 ). In terms of biomass, the ungulates had the biggest biomass and they were represented by the white-lipped peccary (Tayassu pecari Link) with 825 kg/km2 and the tapir (Tapirus terrestris Linnaeus) with 126,6 kg/km2 . Finally, 16 species of food plants were registered in aguajales, most of them inhabiting semi-eutrophic aguajales; of those the aguaje (Mauritia flexuosa L.f.), the shapaja (Scheelea cephalotes Poepp. Ex Mart) and the renacos (Ficus spp.) constituted the most important food resources of whose fruits and seeds fed around 14 species of game mammals.